The existence of serial marriage on the position of children in the issuance of birth certificates - Ardyati, Rizda (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study examines the issue of the issuance of birth certificates for children resulting from unregistered marriages and knowing how the registration that can be made to bring up civil relations between fathers and children resulting from unregistered marriages at the Department of Population and Civil Registration of Semarang Regency. The research was conducted empirically with a descriptive nature, data obtained from primary and secondary data with qualitative analysis techniques. Based on the results of the research and discussion, it is known that the issuance of the Birth Certificate is carried out in three ways, firstly with a statement of children born out of wedlock with the provisions in the Birth Certificate that only the mother's name is included. Second, with the Surat Pertanggungjawaban Mutlak (SPTJM) the truth as a married couple applies the provisions in the Birth Certificate to include the names of the father and mother with additional phrases and thirdly for Muslims after recording the marriage at the KUA with the results of the marriage itsbat trial, then the child is made a Birth Certificate so that his status can be directly recognized son of a legal father and mother. Registration that can be made to bring up civil relations between fathers and children as a result of unregistered marriages are carried out in two ways, first if the marriage cannot be registered then the provisions for child recognition are enforced with a statement of child acknowledgment made by the biological father approved by his biological mother without trial. The second is the ratification of the child by registering the unregistered marriages first and then the trial of the ratification of the child